A Theoretical Model of How Digital Platforms for Public Consultation Can Leverage Deliberation to Boost Democratic Legitimacy - John Gastil (Journal of Deliberative Democracy)
The declining legitimacy of public institutions imperils modern democratic systems, yet deliberative remedies to this problem have not undergone systematic testing. The emergence of robust civic tech provides an opportunity to trace deliberation’s effects on legitimacy. Online civic platforms connecting large publics with democratic governments enable researchers to test the strength of each link that leads from public engagement to institutional legitimacy by way of deliberation. I present such a theoretical model of these linkages and specify sets of working hypotheses regarding public participation, deliberative quality, decision quality, government responsiveness, institutional legitimacy, and opportunities for empowered public engagement.